Rs aggarwal solutions
Our top 5% students will be awarded a special scholarship to Lido.

Factorization of Polynomials | Factorization of Polynomials Exercise 3C

Question 60

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Looking to do well in your science exam ?  
Learn from an expert tutor. Book a free class!

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Let us consider 2a – b = c

So we get,

= 9𝑐^2 − 4𝑐 − 13

We can further write it as

= 9𝑐^2 − 13𝑐 + 9𝑐 − 13

By taking out the common terms

= c (9c – 13) + 1 (9c – 13)

= (c + 1) (9c – 13)

Let us replace c by 2a – b

So we get,

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Then,

= ((2a – b) + 1) (9(2a – b) – 13)

= (2a – b + 1) (18a – 9b – 13)

Set your child up for success with Lido, book a class today!

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta

Question 60

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Looking to do well in your science exam ? Learn from an expert tutor. Book a free class!

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Let us consider 2a – b = c

So we get,

= 9𝑐^2 − 4𝑐 − 13

We can further write it as

= 9𝑐^2 − 13𝑐 + 9𝑐 − 13

By taking out the common terms

= c (9c – 13) + 1 (9c – 13)

= (c + 1) (9c – 13)

Let us replace c by 2a – b

So we get,

9(2𝑎 − 𝑏)^2 − 4(2𝑎 − 𝑏) − 13

Then,

= ((2a – b) + 1) (9(2a – b) – 13)

= (2a – b + 1) (18a – 9b – 13)

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta
Connect with us on social media!
2021 © Quality Tutorials Pvt Ltd All rights reserved
`